Triple-shrine Temple to the northwest of Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
This is an east-facing view of the side shrine from the Triple-shrine Temple in the Mahanaleshwar temple complex. The core of the shikhara (superstructure) of the temple is composed of bricks.